Evolution of the Boolean function manipulation - Sim, Poh Ching; Chin, Kui Fern; Suaidi, M.K (IEEE, 2002)
Solving large systems of Boolean equations is a hard combinatorial problem. It can be greatly facilitated by preliminarily reducing the number of roots in separate equations which, in turn, leads to a reduction in the number of variables, equations and time complexity. This can have a significant effect upon the physical space and connectivity of electronic logic circuits when these are implemented using actual electronic devices or components. In this paper, we review various representation techniques, Boolean function manipulation issues and problems that are used in a practical design environment for digital systems design.